Establishing the Relationship of Static And Dynamic Balance Parameters in 10-12-Year-Old Soccer Players - B. Oprea; L.E. Mihailescu; F. Cojanu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The aim of the paper is to establish the relationship between static and dynamic balance parameters in young soccer players aged 10-12. Methods. An exploratory study was organized with a group of 10-12-year-old soccer players of the School Sports Club no. 1 of Bucharest. The bipedal balance was assessed using the Sensamove Mini Board. The relationship of the static and dynamic balance parameters was determined with the Pearson’s correlation coefficient. Tests applied: Test 1 - static balance (SB), Test 2 – lateral dynamic balance (LDB), and Test 3 - vertical dynamic balance (VDB). Measured parameters: performance, front and back inside (LDB), left and right inside (VDB), left and right avg. deviation. The assessment results highlighted the level of balance development in 10-12-year-old soccer players and the correlations between their parameters